2023
DOI: 10.3390/ijms24065087
|View full text |Cite
|
Sign up to set email alerts
|

Ovariectomy Exacerbates Acute Ethanol-Induced Tachycardia: Role of Nitric Oxide and NMDA Receptors in the Rostral Ventrolateral Medulla

Abstract: Ethanol consumption influences cardiovascular functions. In humans, acute consumption of ethanol causes dose-dependent tachycardia. Our previous study showed that ethanol-induced tachycardia might involve decreased nitric oxide (NO) signaling in the brain’s medulla. NMDA receptors, another important target of ethanol, are one of the upstream signals of nitric oxide. Reports showed the modulation of NMDA receptor function by estrogen or estrogen receptors. The present study aims to examine the hypothesis that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…They also impair NMDA receptor activity by regulating the protein levels and localization of NMDA receptor subunits [13]. In our previous study, we observed that changes in the levels of phosphorylated serine 896 on the GluN1 subunit of NMDA receptors might involve the estrogen regulation of ethanol effects on NMDA receptor function in the RVLM [34]. In our present study, immunohistochemistry analysis showed no significant changes in the immunoreactivity of pGluN1-serine896 and GluN1 in the RVLM region during the ICV administration of Aβ1-40.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…They also impair NMDA receptor activity by regulating the protein levels and localization of NMDA receptor subunits [13]. In our previous study, we observed that changes in the levels of phosphorylated serine 896 on the GluN1 subunit of NMDA receptors might involve the estrogen regulation of ethanol effects on NMDA receptor function in the RVLM [34]. In our present study, immunohistochemistry analysis showed no significant changes in the immunoreactivity of pGluN1-serine896 and GluN1 in the RVLM region during the ICV administration of Aβ1-40.…”
Section: Discussionmentioning
confidence: 93%
“…The procedure for ICV administration of anesthetized rats was similar to those described in our previous study [33,34]. Adult male Sprague Dawley 8-10 weeks old rats (300-400 g) were used in this experiment under urethane anesthetized (1.2-1.5 g/kg i.p.).…”
Section: Drugs Administration and Blood Pressure Measurementmentioning
confidence: 99%
See 1 more Smart Citation